A hierarchical combinatorial testing method for smart phone software in wearable IoT systems. (July 2017) - Cui, Kai; Zhou, Kuanjiu; Qiu, Tie; Li, Mingchu; Yan, Leiming
Highlights: The hierarchical combinatorial testing method is presented when the structure of the state machine model is complex and large. The CSSCA algorithm is presented which conducts similarity calculation to further divide the decomposed FSMs into sub-models. We propose the shortest regular expression test cases generation method, in which the reduction process is postponed broadcasting. Graphical abstract: Result of first clustered and the connected graph model of the states Abstract: As the Internet of Things technology is finding more wide applications; wearable smart systems such as smart phones have gradually come into our lives. The smart wearable systems with numerous states usually lead to various unanticipated problems. A connective and semantic similarity clustering algorithm (CSSCA) and a hierarchical combinatorial test model based on finite state machine (FSM) are proposed to solve the problem. The FSM model of user manipulations is usually used to model the system design specification of a smart phone for black-box testing, and then it is converted into a regular expression, and some testing cases are generated according to the regular expression. Many experiments show that a large in scale and complicated in structure smart phone software can be tested using our innovative algorithms to discover more deep hidden logical errors efficiently and effectively.